Numerical Investigation on the Effect of the Particle Feeding Order on the Degree of Mixing Using DEM. (2015) - Xiao, Xiangwu; Tan, Yuanqiang; Zhang, Hao; Jiang, Shengqiang; Wang, Jiaqian; Deng, Rong; Cao, Guodong; Wu, Binxing
Abstract: The purpose of this paper is to investigate the effect of the particle feeding order on the degree of mixing in the industrial compound ribbon mixer. The Discrete Element Method (DEM) was adopted to simulate the particle feeding process into industrial compound ribbon mixer from the hopper and the mixing process. Two kinds of particles with different physical properties and sizes were used in the simulations. The diameter of the small particles was uniformly set 18 mm but the diameters of the large particles ranged from 30 mm to 60 mm. The Hertz-Mindlin model was adopted as the interaction rule between the elements. Three feeding orders were considered in the simulations, namely feeding the large particles after the small particles, feeding the small particles after the large particles and feeding well mixed particles. The degree of mixing in each case was evaluated using a mathematical statistical method. The numerical results revealed that feeding the large particles after the small particles can enhance mixing where higher degree of mixing can be obtained than other two cases. The findings in this study can be the indications to the actual industrial production.